Uremic cholangiopathy (Varela Fuentes syndrome): the interest in surgery - Gary, Ruben; Latourrette, Federico; Acosta Ferreira, Walter (Cirugía del Uruguay, 2020)
The present work is the 2nd part of a report on 18 cases of "uregimenous cholangiopathy" (Demeulaneure), primarily marked by th association of obstructive angiocholitis an drenal failure, in the course of actue biliary syndrome.